2017
DOI: 10.1186/s12929-016-0309-5
|View full text |Cite
|
Sign up to set email alerts
|

PPARs modulate cardiac metabolism and mitochondrial function in diabetes

Abstract: Diabetic cardiomyopathy is a major complication of diabetes mellitus (DM). Currently, effective treatments for diabetic cardiomyopathy are limited. The pathophysiology of diabetic cardiomyopathy is complex, whereas mitochondrial dysfunction plays a vital role in the genesis of diabetic cardiomyopathy. Metabolic regulation targeting mitochondrial dysfunction is expected to be a reasonable strategy for treating diabetic cardiomyopathy. Peroxisome proliferator-activated receptors (PPARs) are master executors in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 77 publications
2
62
0
Order By: Relevance
“…Some authors speculate that the upregulation of the nuclear receptor transcription factor PPARα and its coactivators PGC-1α/β is one of the preliminary requirements for metabolic switch from glucose to FA consumption in IR and diabetic hearts (Schilling, 2015 ; Lee et al, 2017 ). This agrees with an increased level of PPARα as well as the total (+38%) and sarcolemmal (+26%) FAT/CD36 content in the diabetic animal hearts (Mansor et al, 2017 ).…”
Section: Fatty Acid Transporter Proteinsmentioning
confidence: 99%
“…Some authors speculate that the upregulation of the nuclear receptor transcription factor PPARα and its coactivators PGC-1α/β is one of the preliminary requirements for metabolic switch from glucose to FA consumption in IR and diabetic hearts (Schilling, 2015 ; Lee et al, 2017 ). This agrees with an increased level of PPARα as well as the total (+38%) and sarcolemmal (+26%) FAT/CD36 content in the diabetic animal hearts (Mansor et al, 2017 ).…”
Section: Fatty Acid Transporter Proteinsmentioning
confidence: 99%
“…PPARs are transcription factors that increase the expression of genes involved in fatty acid oxidation. On the other hand, the expression of several genes involved in glucose catabolism are decreased by PPARs ( 2 , 10 ).…”
Section: The Metabolic Flexibility Of the Healthy Heartmentioning
confidence: 99%
“…Reducing PGE2 production by INDO inhibited M2 polarization thus INDO shared a similar PPARG activation response with AA ( Fig 4F). To formally address the possibility of PPARG bridging AA/PGE2 mediated M2 macrophage polarization, we isolated bone marrow derived monocytes (BMDM) from wild type (WT, Pparg (Lee et al, 2017). Collectively, these data revealed that PGE2 enhanced OXPHOS during M2 polarization and PPARG de-activation participated in this process.…”
Section: Pge2 Inhibits Pparg Resulting In M2 Macrophage Polarizationmentioning
confidence: 99%
“…Metabolic reprogramming of tumor microenvironment (TME) by cancer cells provide a perfect example of how metabolism interplay with immune function (Pavlova and Thompson, 2016). Cancer cells released lactate, glutamine, succinate and α-ketoglutarate (α-KG) help T cell and macrophage polarize towards immunosuppressive phenotype (Angelin et al, 2017, Chen et al, 2017, Mehla and Singh, 2019. In contrast, metabolic reprogramming of the TAM inhibited tumor progression by allowing the accumulation of T cell receptor engineered T cells (Stromnes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%